25-3x=7-9x

Simple and best practice solution for 25-3x=7-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25-3x=7-9x equation:


Simplifying
25 + -3x = 7 + -9x

Solving
25 + -3x = 7 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
25 + -3x + 9x = 7 + -9x + 9x

Combine like terms: -3x + 9x = 6x
25 + 6x = 7 + -9x + 9x

Combine like terms: -9x + 9x = 0
25 + 6x = 7 + 0
25 + 6x = 7

Add '-25' to each side of the equation.
25 + -25 + 6x = 7 + -25

Combine like terms: 25 + -25 = 0
0 + 6x = 7 + -25
6x = 7 + -25

Combine like terms: 7 + -25 = -18
6x = -18

Divide each side by '6'.
x = -3

Simplifying
x = -3

See similar equations:

| 7x-2(2x+6)=6 | | 3x+(x+2)=33 | | 98-(7x+11)=7(x+6)+x | | 3x+2x=33 | | 98-(7x+11)=7(7x+6)+x | | 98-(7x+11)=7(7x+6)+6 | | 7(8t+1)-15=t-(t+7) | | 4(5t+1)-7=t-(t+2) | | 5(3x+4)-2x=7x-(-2x+11) | | 4(5t-1)-7=t-(t-2) | | 3x+5(2x-7)=4 | | 25x+20=3x+10 | | -2(x)=5x-5-x | | 12-a=5a | | 4.5*x=0.1 | | 4.5*x=1 | | 4.5*x=0.5 | | 4.5*x=0.7 | | 3v+2=7v+6 | | 2+3*5-2= | | f(n)=7n-1 | | x-60=-60 | | 22-22= | | 24x=595 | | 10x+0.5x=21 | | 301.5656=4*3.14r^2 | | x=2(47)+2(116) | | 9988.2144=4*3.14r^2 | | 669.3224=4*3.14r^2 | | 1/3(12x)=-24 | | -15+5/6x=50 | | Y=21+4y |

Equations solver categories